Preliminary investigation of anti-fatigue effects and potential mechanisms of meiju oral liquid in mouse and zebrafish models - Lanlan Zhang; Jingcheng Zhao; Xi Zhou; Maitinuer Maiwulanjiang (PLoS ONE, 2025)
Meiju Oral Liquid (MOL), a representative medicinal formula in China, stems from the traditional use of specific Chinese medicinal herbs known for their anti-fatigue properties, including rose, jujube, chicory, and wolfberry. While these individual herbs have been recognized for their benefits, the formulation of MOL itself has not been extensively studied. This study was designed to evaluate the potential anti-fatigue effects of MOL, prepared from these natural herbs, and to explore its underlying mechanisms. In this research, both mouse and zebrafish models were utilized to investigate the anti-fatigue effects of MOL. Chemical characterization of MOL and identification of bioactive compounds in serum were conducted using ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF/MS). The results demonstrated that MOL significantly prolonged the weight-bearing swimming time in mice, increased hepatic and muscle glycogen content, and reduced serum levels of blood urea nitrogen, blood lactate, and inflammatory markers (IL-1β, IL-6, TNF-α, and NO). Furthermore, MOL down-regulated the expression of NOX4 and TNF-α proteins while up-regulating p-PI3K and p-AKT proteins in the liver tissues of fatigued mice. In zebrafish models, MOL exhibited protective effects against sodium sulfite-induced lethality, enhanced high-speed motion trajectories, and increased movement distances in both normal and fatigued zebrafish. Additionally, MOL downregulated IL-1β, IL-6, TNF-α, and TNF-β mRNA levels while up-regulating PI3K and AKT1 mRNA levels in fatigued zebrafish. These findings suggested that the anti-fatigue effects of MOL may be mediated through the activation of the PI3K/AKT signaling pathway as well as the inhibition of TNF-α and NOX4 expression. In addition, a total of ninety-four chemical components were identified in MOL, with twenty-three migration compounds detected in mouse serum. These migration compounds are likely the primary active agents, contributing to the reduction of metabolite accumulation, enhancement of glycogen synthesis, and suppression of inflammatory responses. Taken together, our findings underscore the potential anti-fatigue effects of MOL, warranting further investigation into its therapeutic applications and the specific roles of its bioactive compounds.